Utilização de múltiplas de superfície livre no imageamento sísmico - SANTOS, Isis Tourinho dos (Universidade Federal do Pará, 2019)
Conventional seismic processing treats multiple reflections as noise, removing them from the imaging process. However, multiple reflections have different propagation wave paths from primary reflections and thus can be used to illuminate areas not illuminated by primary reflections. Consequently, migration of multiples can arise as possibility of imaging of complex structures in the subsurface. In this context, this work shows a abstract about the most relevant approaches from the imaging using multiples. In addition, this work shows results with free-surface multiples used in seismic imaging by reverse time migration.